Analisis Perbandingan Standar Audit Internasional (ISA) dengan Standar Audit Indonesia dalam Perspektif Teoretis - Yasmin Darmawan Nusa; Yunita Zahra; Fikri Rizki Utama (Indo Publishing, 2026)
This study aims to analyze the comparison between International Standards on Auditing (ISA) and Indonesian audit standards from a theoretical perspective, and to examine the implications of harmonizing the two standards on audit quality. The research method used is library research with a descriptive qualitative approach. Data were obtained from various literature sources, such as books, scientific journals, Public Accountant Professional Standards (SPAP), International Standards on Auditing (ISA), as well as regulations and previous research relevant to the research topic. The analysis was conducted by comparing the basic concepts, audit procedures, and implementation of the two audit standards. The results show that ISA and Indonesian audit standards have the same objective of improving audit quality and the credibility of financial reports, but they differ in their implementation approaches. ISA emphasizes a principle-based and risk-based auditing approach that provides more room for the use of auditor professional judgment, while Indonesian audit standards tend to be more rule-based and procedural. Harmonization of ISA with Indonesian audit standards has a positive impact on increasing transparency, accountability, and the quality of audit results in Indonesia. However, the implementation of this harmonization still faces various challenges, such as limited auditor competence, human resource readiness, and differences in regulatory conditions and organizational culture. Therefore, it is necessary to improve the quality of professional education, auditor training, and strengthen professional oversight to support the optimal implementation of international auditing standards in Indonesia.